Pengaruh Penguat Hibride Partikel Serbuk Arang Sekam Padi dan Kalsit Terhadap Sifat Mekanik pada Komposit Polyester Resin - Basmal; Joko Sukarno; Siswanto (Politeknosains, 2017)
The study entitled "Strengthening Effect of Particle Hibride Charcoal Rice Husk Powder and Mechanical Properties of Calcite Against On Polyester Resin Composites" aims to determine the effect of the volume fraction of filler partkel hibride the mechanical properties of composite properties. Mechanical properties of the composite hibride researched include flexural strength properties of the standard ASTM D 790, Impact strength properties of the standard ASTM D 5941 and ASTM standard fuel properties ktahanan D 635.dan SEM fracture morphology to determine the composite. Matrix composites using Unsaturated Polyester Resin BQTN 157, Filler hibride using rice husk charcoal powder and powder kalisit 60-80 mesh 100-120 mesh with a total weight of the filler fraction of 50%. Percentage ratio between the weight fraction of filler hibride rice husk powder and powder calcite are: 15:35, 20:30, 25: 25, 30:20. MEKP hardener using 1 wt% Matrix Resin. Material is mixed using a mixer rotation of 100 rpm for 5 minutes. Making composite by means poured into the mold by holding time of 30 minutes. Composite specimens given rain water immersion treatment for 20 days. The test results in getting the highest mechanical properties of the composite specimens: The flexural strength 95.54 N / mm2, the impact strength of 5.97 kJ / mm2, and fuel resistance properties rate of 0.10 mm / sec. Lowest mechanical properties is obtained: The flexural strength 84.17 N / mm2, the impact strength of 5.10 kJ / mm2, and fuel resistance properties rate of 0.19 mm / sec.